The impact of long-term care insurance in China on beneficiaries and caregivers: A systematic review - Simiao Chen; Linye Li; Juntao Yang; Lirui Jiao; Todd Golden; Zhuoran Wang; Haitao Liu; Peixin Wu; Till Bärnighausen; Pascal Geldsetzer; Chen Wang (Journal of Global Health Economics and Policy)
# Background